Adjusting Class Policies amid a Pandemic: How Lessons Learned During COVID-19 Can Help Faculty Prepare for Other Institution-Wide Crises - Holtzman, Mellisa; Whitehead, Ellen; Welch, Ayrlia (Teaching and Learning Inquiry, 2023)
Research consistently suggests that student learning is maximized when faculty balance stringency and leniency in their classroom policies. However, the COVID-19 crisis raised an important question: In the face of a wide-scale crisis, should faculty instead adopt forgiving policies? This study uses interview data with 43 university faculty across the United States to examine policy adjustments made in response to COVID-19, as well as the impact faculty felt those adjustments had on course learning objectives. Results suggest that even amid a wide-scale crisis, balancing leniency and stringency offers benefits to both students and instructors. Implications for future crisis-response and crisis-preparedness are also discussed. Click here to read the corresponding ISSOTL blog post.